Demographic Dividends in the South', Ageing North', and South-South' Trade Diversification - Georges, Patrick; Seckin, Aylin (Routledge Journals, Taylor & Francis Ltd, 2016)
The absence of clear convergence in incomes per capita and welfare between the North and the South, even in the face of spectacular growth rates in GDP in the emerging South, might be due to a terms of trade deterioration resulting from an expansion of production in the South which depresses the product's price on world markets. This may originate from a technical catch up and also from a demographic dividend in the South relative to an ageing North. This article illustrates that some South-South trade diversification might mitigate the terms of trade deterioration and increase welfare gains in the South. We use a multicountry overlapping-generation general equilibrium model to simulate the magnitude of the terms of trade effect due to a demographic dividend in Turkey, and show that some trade diversification away from EU toward the South is a welfare improving policy for Turkey.
Keywords: Ageing; Demographic Dividend; General Equilibrium Modelling; Overlapping Generation Modelling; Trade Policy; Turkey